Cell‐intrinsic timing in animal development. (24th July 2014) - Moss, Eric G.; Romer‐Seibert, Jennifer
Abstract In certain instances we can witness cells controlling the sequence of their behaviors as they divide and differentiate. Striking examples occur in the nervous systems of animals where the order of differentiated cell types can be traced to internal changes in their progenitors. Elucidating the molecular mechanisms underlying such cell fate succession has been of interest for its role in generating cell type diversity and proper tissue structure. Another well‐studied instance of developmental timing occurs in the larva of the nematode Caenorhabditis elegans, where the heterochronic gene pathway controls the succession of a variety of developmental events. In each case, the identification of molecules involved and the elucidation of their regulatory relationships is ongoing, but some important factors and dynamics have been revealed. In particular, certain homologs of worm heterochronic factors have been shown to work in neural development, alerting us to possible connections among these systems and the possibility of universal components of timing mechanisms. These connections also cause us to consider whether cell‐intrinsic timing is more widespread, regardless of whether multiple differentiated cell types are produced in any particular order. For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.